2015
DOI: 10.1111/mec.13494
|View full text |Cite
|
Sign up to set email alerts
|

Paternal intergenerational epigenetic response to heat exposure in male Wild guinea pigs

Abstract: Epigenetic modifications, of which DNA methylation is the best studied one, can convey environmental information through generations via parental germ lines. Past studies have focused on the maternal transmission of epigenetic information to the offspring of isogenic mice and rats in response to external changes, whereas heterogeneous wild mammals as well as paternal epigenetic effects have been widely neglected. In most wild mammal species, males are the dispersing sex and have to cope with differing habitats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 50 publications
4
66
1
Order By: Relevance
“…Comparing with the annual mean temperature and salinity, recent studies emphasized that changes of maximum and minimum values may have greater effects on ascidians (Stachowicz, Terwin, Whitlatch, & Osman, ). Studies on both plants and animals suggest that the environmental stresses can be associated with long‐term epigenetic modifications, which can be transmitted through generations (Jablonka, ; Weyrich et al., ). Thus, the matrix of environmental factors was represented by the raw data of six environmental factors including annual water temperature, maximum water temperature, minimum water temperature, annual water salinity, maximum water salinity, and minimum water salinity.…”
Section: Methodsmentioning
confidence: 99%
“…Comparing with the annual mean temperature and salinity, recent studies emphasized that changes of maximum and minimum values may have greater effects on ascidians (Stachowicz, Terwin, Whitlatch, & Osman, ). Studies on both plants and animals suggest that the environmental stresses can be associated with long‐term epigenetic modifications, which can be transmitted through generations (Jablonka, ; Weyrich et al., ). Thus, the matrix of environmental factors was represented by the raw data of six environmental factors including annual water temperature, maximum water temperature, minimum water temperature, annual water salinity, maximum water salinity, and minimum water salinity.…”
Section: Methodsmentioning
confidence: 99%
“…Most individuals within a given natural population usually experience exposure to an environmental stressor at the same time and in the same extent (Burggren, ). When a group of organisms is exposed to a certain stressor, the same epigenetically determined phenotypes are known to be consistently acquired (Feil & Fraga, ; Klironomos, Berg, & Collins, ; Manjrekar, ), confirming that a given environmental stressor can thrive into the same epigenetic modifications (and their resulting phenotypes) in the different exposed organisms (Burggren, ; Weyrich et al., ). Furthermore, the analysis of DNA methylation in wide‐ranging taxa revealed that the patterns of DNA methylation are conserved across deep phylogenies (Mendizabal, Keller, Zeng, & Yi, ; Sarda, Zeng, Hunt, & Yi, ; Suzuki, & Bird, ); and the genomic regions that reflect divergence of DNA methylation between related species seem to be enriched for both tissue and development specializations (Hernando‐Herraez et al., ; Mendizabal et al., ; Wang, Cao, Zhang, & Su, ).…”
Section: Epigenetic Mechanisms and Their Evolutionary Rolementioning
confidence: 98%
“…(), investigating the response of wild guinea pigs ( Cavia aperea ) to rising temperatures. The authors exposed adult male guinea pigs (F0) to an increased ambient temperature and then compared the liver (as the main thermoregulatory organ) of the F0 fathers and F1 progeny, finding “an ‘immediate’ and ‘heritable’ epigenetic response” (Weyrich et al., ). More precisely, differentially methylated patterns were noticed in the exposed F0 organisms and transferred to the subsequent F1 generation.…”
Section: Epigenetic Contribution For the Adaptation To Climate Changementioning
confidence: 99%
“…At a cellular/molecular level, exposure to acute hyperthermia can result in long‐term effects on cellular function and epigenetics (Weyrich et al . 2016) that may remain hidden until exposure to a secondary stress or in response to long‐term processes associated with ageing (Velichko et al . 2015).…”
Section: Introductionmentioning
confidence: 99%